Writers’ Block for Writers: How Far is it True? - Rahmat, Noor Hanim (Global Journal of Social Sciences Studies, 2020)
Writer’s block may be temporary or permanent for writers; depending on how they (writers) respond to the block. Some take measures to overcome while some chose to “rest “ from writing. Among some of the causes of writers’ block are the writer’s attitude towards writing-related activities and writers’ lack of content and rhetorical knowledge. The objective of this study is to investigate the possible causes of writers’ block. Specifically, this study looked into how writing process influenced writers’ block. This study also explored how writing fear influenced writer’s block. 29 academicians participated in this mixed mode research. Participants responded to a survey and data was quantitatively and qualitatively analysed. Findings revealed that writers suffer from writers’ block because they crave for perfection when they write. In addition to that, writers sometimes block themselves from writing because of their won perception of themselves and what writing entails. These findings have interesting implications towards managing writers’ block among academicians.